ADMINISTRATIVE PERSONNEL SELECTION OF KAMBANGAN VILLAGE IN BRUNO DISTRICT, PURWOREJO REGENCY - Agus Dwi Atmoko; Pratika Ayuningtyas; Lutfi Ashar Mauludin (Darmabakti Cendekia: Journal of Community Service and Engagements, 2022)
Background: As an independent institution, Politeknik Sawunggalih Aji is trusted to hold one of the three requirements of administrative personnel selection, which is a Computer skill test. Objective: The aim is to conduct a computer skill test as one of three requirements of organizational personnel selection Method: Computer Skill test includes the mastery of Ms. Word, Ms. Excel, and Ms. PowerPoint. Results: The total score of the participants' test is qualified. Conclusion: The test is well run. The computer test is valued at 30% of the total score of the three requirements.